ANALISIS KUALITAS PELAYANAN KAPAL TELUK SINABANG SEBAGAI JALUR PENGEMBANGAN WISATA BAHARI RUTE LABUHAN HAJI-SIMEULUE - Veranita Veranita; Ferdi Saputra (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2016)
Along with the progress and the growing number users of transport services, companies engaged in the transportation services required to improve the quality of its services, one of which is the perception of the quality service to passengers transport used by consumers. Quality of service is a service of the vessel Kmp.Teluk rated Sinabang these Labuhan Haji- Simeulue. The analysis was performed by calculating the Importance Performance Analysis (IPA). The purpose of this research is to identify some of the factors that influence perceptions of service and the level of conformity respondent / passenger sea transportation of Sinabang Kmp.teluk vessel analysis using Perception Index. Analysis of the results of Importance Performance Analysis to come by researchers at the Level of Performance Boats for Suistability Respondent (Tki) 0:09, the assessment Perception by Level of Performance Boats obtained results Suistability Respondent (Tki) 2:33, and the assessment Perception by Importance obtained results Suistability respondents (Tki) 1:00. So the importance of the overall results and performance in getting results overall passenger perception of Conformity Level Respondents 73.94 = 74 (Tki 74%). Suistability respondents (Tki) is the result of statements that prove the hypothesis if the value of the average performance of the above as well as the average value of importance/ expectations in the level of suitability of respondents freight ferries KMP.Teluk Sinabang under Tki <100%, which means transport services KMP.Teluk Sinabang not satisfactory. Keyword : Service, Sea Transportation, Importance Performance Analysis